Choosing Psychiatry as a Career: Motivators and Deterrents at a Critical Decision-Making Juncture. (August 2014) - Wiesenfeld, Lesley; Abbey, Susan; Takahashi, Sue Glover; Abrahams, Caroline
Objective: To examine factors influencing the choice of psychiatry as a career between residency program application and ranking decision making. Methods: Using an online questionnaire, applicants to the largest Canadian psychiatry residency program were surveyed about the impact of various factors on their ultimate decision to enter psychiatry residency training. Results: Applicants reported that patient-related stigma was a motivator in considering psychiatry as a career, but that negative comments from colleagues, friends, and family about choosing psychiatry was a deterrent. Training program length, limited treatments, and insufficient clerkship exposure were noted as deterrents to choosing psychiatry, though future job prospects, the growing role of neuroscience, and diagnostic complexity positively influenced choosing psychiatry as a specialty. Research and elective time away opportunities were deemed relatively unimportant to ranking decisions, compared with more highly weighted factors, such as program flexibility, emphasis on psychotherapy, service–training balance, and training program location. Most applicants also reported continuing to fine tune ranking decisions between the application and ranking submission deadline. Conclusions: Stigma, exposure to psychiatry, diagnostic complexity, and an encouraging job market were highlighted as positive influences on the choice to enter psychiatry residency. Interview and information days represent opportunities for continued targeted recruitment activity for psychiatry residency programs.